Optimal control and stability analysis of an epidemic model with population dispersal. (February 2016) - Jana, Soovoojeet; Haldar, Palash; Kar, T.K.
Highlights: SEIR type epidemic model with population dispersal is considered here. Vaccination is taken as a control parameter. Optimal control problem is formulated and then solved. Simulation shows that different diseases can be analyzed through this model. Abstract: In the present paper we consider an SEIR type epidemic model with transport related infection between two cities. It is observed that transportation among regions has a strong impact on the dynamic evolution of a disease which can be eradicated in the absence of transportation. Transportation can lead to the incorporation of a positive risk probability. The epidemiological threshold, commonly known as the basic reproduction number, is derived and it is observed that when the basic reproduction number is less than unity the disease dies out, where as if it exceeds unity the disease may persist in the system. A thorough dynamical behavior of the constructed model is studied. We formulate and solve an optimal control problem using vaccination as a control tool. Extensive numerical simulations are carried out based on our analytical results. Finally we try to relate our work with a real world problem.